The history of British birds - Yalden, D. W. (Oxford ornithology series., 2009)
"The History of British Birds reviews our knowledge of avifaunal history over the last 15,000 years, setting it in its wider historical and European context. The authors, one an ornithologist the other an archaeologist, integrate a wealth of archaeological data to illuminate and enliven the story, indicating the extent to which climatic, agricultural, and social changes have affected the avifauna. They discuss its present balance, as well as predicting possible future changes." "It is a popular misconception that bird bones are rarely preserved (compared with mammals), and cannot be reliably identified when they are found. The book explores both of these contentions, armed with a database of 9,000 records of birds that have been identified on archaeological sites. Most are in England, but sites elsewhere in Great Britain, Ireland, the Isle of Man, and the Channel Isles are included." "This authoritative reference work will be of particular relevance to students and researchers in the fields of archaeology and avian biology, as well as a broader audience of general ornithologists and natural historians."--Jacket.